An outer-sphere two-electron platinum reagent - Jude, Hershel; Krause Bauer, Jeanette A; Connick, William B (Journal of the American Chemical Society, 2003)
A strategy for designing cooperative outer-sphere two-electron platinum reagents is demonstrated. The novel platinum(II) complex, [Pt(tpy)(pip2NCN)][BF4] (1(BF4-)) (tpy = 2,2':6',2' '-terpyridine, pip2NCN- = 2,6-(CH2N(CH2)5)2-C6H3-), in which the metal is bonded to two pincer type ligands, has been prepared. Treatment of 1 with protic acid results in protonation of the pendant piperdyl groups, allowing for the isolation of [Pt(tpy)(pip2NCNH2)][PF6]3 (2(PF6-)3). 1H NMR spectra of 1 and 2 establish that in each complex the terpyridyl ligand is tridentate, whereas the piperdyl ligand is monodentate, bonded to platinum through the phenyl ring. The structure of the protonated complex was confirmed by an X-ray crystallographic study of crystals of 2(Cl-)3.4H2O. The cyclic voltammagram of 1 exhibits two reversible one-electron reduction waves at E degrees ' = -0.98 V and E degrees ' = -1.50 V (E degrees ' = (Epc + Epa)/2), with a DeltaEp of 65 and 61 mV, respectively. In contrast to other Pt(II) complexes, including 2, this complex also undergoes a nearly reversible two-electron oxidation process at E degrees ' = 0.40 V (DeltaEp = 43 mV, 0.01 V/s). The accumulated data are consistent with the unusual ligand architecture of 1 being capable of stabilizing and allowing for facile interconversion between the Pt(II) and Pt(IV) oxidation states.